Answer:
m=(-6,6)
Step-by-step explanation:
m^2 -36 = 0
Reorder the terms:
-36 + m^2 = 0
Solving for variable 'm'.
Add '36' to each side of the equation.
-36 + 36 + m^2 = 0 + 36
Combine like terms: -36 + 36 = 0
0 + m^2 = 0 + 36
m^2 = 0 + 36
Combine like terms: 0 + 36 = 36
m^2 = 36
Simplifying
m^2 = 36
Take the square root of each side:
√m^2=+/-√36
m=(+/-)6
m = {-6, 6}
let the width of the rectangle be x
area of rectangle is l*b
x * (x + 6) = 40^2
x^2 + 6x = 40^2
x^2 + 6x = 1600
x + 6x =√1600
x + 6x = 40
7x = 40
x = 5.7
Hope you found this useful
Answer: 250 years
Step-by-step explanation:
12/3=4
4 x $1 = $4 per year
$1000/4=250
250 years
I believe the answer is C
Answer:
x,y = 13/3, -10/3
Step-by-step explanation:
8x+8y=8
8x+2y=28 Subtract eq1 by eq 2
6y=-20
y=-20/6 y = -10/3
8x - 80/3=8
8x=34 2/3
x=4 1/3
x=13/3
Hope this helps plz hit the crown :D